Progress report on fish health: project collaborations between FRI (NaFisH, FRITD, FRIGL) & IPTA (UPM, IIUM, UMK) 2018-2020 - Abdullah, Azila (Fisheries Research Institute (FRI), 2022)
Progress report on fish health project collaboration extends the results of the FRI and IPTA researcher's cumulative efforts over the 3 years (2018-2020) of the study. The purpose of publishing this report is to ensure all the information and methods used in this research program are properly documented so that it can be used as a guide and reference for researchers, fisheries managers, and public university students, particularly in Malaysia. It is hoped that through the findings and recommendations submitted, better management strategies can be implemented to ensure a more sustainable aquaculture industry in Malaysia.